THE INFLUENCE OF THE IMPLEMENTATION OF REGIONAL AUTONOMY ON REGIONAL FINANCIAL MANAGEMENT OF EAST KALIMANTAN PROVINCE - Baren Sipayung; Rido Doly Cristian (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
This article explains the essence, purpose, benefits for the region and the current development of regional autonomy and its practice in East Kalimantan. In this article, criticizing theoretically by concocting various data/theories being criticized is complemented by references to several relevant journals. Furthermore, analysis related to policy implementation by identifying various problems and challenges faced, as well as providing solutions on how to realize regional autonomy in East Kalimantan Province. In terms of applying the principles of regional financial management efficiently, economically, effectively, transparently, and responsibly by taking into account the sense of justice, propriety, and benefits for the community as well as the implementation of performance-based budgeting, the setting of cost standards in the imposition of Regional Expenditures is a form of financial management discretion. area by the Regional Government as long as it fulfills the provisions related to the designation, use, and conditions for the application of discretion as regulated in Law Number 30 of 2014 concerning Government Administration.